INSPECTORATE SUPERVISION PERFORMANCE IN THE UTILIZATION OF BOS FUNDS IN THE PROVINCE OF SOUTH SUMATRA IN 2022 - Vibio Pratama, M. Fernanda; Kariem, M. Quranul; Febriyanti, Doris (CV. Era Digital Nusantara, 2022)
This study describes the school operational assistance program (bos) which is a government program that basically provides funding for non-personnel operating costs for basic education units as implementers of the compulsory education program. According to PP Number 48 of 2008, what is meant by